2014
DOI: 10.3389/fgene.2014.00380
|View full text |Cite
|
Sign up to set email alerts
|

Replication of obesity and diabetes-related SNP associations in individuals from Yucatán, México

Abstract: The prevalence of type 2 diabetes (T2D) is rising rapidly and in Mexicans is ~19%. T2D is affected by both environmental and genetic factors. Although specific genes have been implicated in T2D risk few of these findings are confirmed in studies of Mexican subjects. Our aim was to replicate associations of 39 single nucleotide polymorphisms (SNPs) from 10 genes with T2D-related phenotypes in a community-based Mexican cohort. Unrelated individuals (n = 259) living in southeastern Mexico were enrolled in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In the presently analyzed population, rs5218 had a MAF of 0.209 and rs5219 had a MAF of 0.329. Similarly, two previous studies analyzing the Mestizo population of Mexico City were unable to identify an association between rs5219 and T2DM ( 20 , 21 ). In particular, the frequency of the risk allele was shown to be too low to reach the power in order to detect an association ( 20 ).…”
Section: Discussionmentioning
confidence: 81%
“…In the presently analyzed population, rs5218 had a MAF of 0.209 and rs5219 had a MAF of 0.329. Similarly, two previous studies analyzing the Mestizo population of Mexico City were unable to identify an association between rs5219 and T2DM ( 20 , 21 ). In particular, the frequency of the risk allele was shown to be too low to reach the power in order to detect an association ( 20 ).…”
Section: Discussionmentioning
confidence: 81%
“…CDKN2A/B genes are expressed in adipocytes and pancreatic islets and play a role in β-cell function and regeneration. The polymorphism rs10811661 located 125 kb upstream of these genes has been identified as a risk allele in a contemporaneous Mayan population [ 25 ] containing lower rates of dispersion and a high predisposition to obesity, diabetes and consanguineous marriage [ 26 ]. Our results showed no statistically significant difference in allele frequency of this variant compared to HapMap and the 1000 Genomes Project, or with any of the traits related to T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing exact data was occasionally hampered by flaws in some studies, where SNP alleles were not reported, or tables and text have not been in agreement [54,134]. Determining DNA strand specificity and reporting the respective minor and major alleles is easy for A/G, A/C, T/G, and T/C base exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…A significant association between plasma leptin and rs5219 (G/A, missense variant p.E23K) of potassium channel, inwardly rectifying subfamily J, member 11 (KCNJ11) was found in a population from Yucatan, Mexico [54]. Carriers of the A-allele exhibited higher serum leptin levels.…”
Section: Leptin (Lep)mentioning
confidence: 99%